Analisa Pengaruh Desain Grafis pada Konten Media Sosial terhadap Daya Tarik Pengguna dari Generasi Z di Kota Batam - Surya Tjahyadi; Willy Antonio (Departement of Mathematics Education, 2023)
Social media is one of the technological developments that has a big contribution in making it easy for humans to communicate and socialize. The high use of social media raises various graphic designs to attract its users. Therefore, many social media users use graphic designs in their content. This study aims to determine the effect of graphic design on social media content on the attractiveness of users from generation z. The results of this study indicate that the application of graphic design to social media content greatly influences the attractiveness of social media users from generation z.